A Historical Overview of Protected Agriculture in the State of Sinaloa, Mexico: Implications for Improving Rural Prosperity - Luis A. Flores; Craig M. Edwards (Journal of International Agricultural and Extension Education, 2019)
Economic development is an important phenomenon that can positively impact societal problems such as poverty, lack of education, and insufficient infrastructure, among other ills. In this regard, technological advances are essential to making better use of resources. The agricultural sector is no exception. With the passage of time, advances in agriculture have allowed processes to be optimized, improving production practices and minimizing risks, by using innovative technologies (Schenkel, Finley, & Chumney, 2012). For this reason, the adoption and use of approaches to protected agricultural production grew steadily in the State of Sinaloa, Mexico during the last century and until today. Such technology assisted significantly in the economic development of the region. This inquiry sought to understand factors and forces that augmented expansion of protected agriculture, especially regarding tomato production, and its advantages compared to traditional systems, as experienced by producers in Sinaloa. Understanding such a phenomenon may provide important implications for improving the economies of similar contexts in need of economic development where agriculture is a viable sector
Keywords: economic development; protected agriculture; Sinaloa tomato industry; technological innovation